PENILAIAN KESEHATAN BMT AT-TAQWA MUHAMMADIYAH SUMATERA BARAT - M. ZAKY MUBARAK LUBIS; BAYU ANDRI YATMA (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to determine the health level of BMT At-Taqwa Muhammadiyah West Sumatra in 2014-2016 based on the regulation of the Minister of Cooperatives and Small and Medium Enterprises of RI No.07 / per / Dep.6 / IV / 2016 concerning aspects of capital, productive asset quality, efficiency , liquidity and compliance with sharia principles. This research type is descriptive evaluation research. The subject of the study was the At-Taqwa Muhammadiyah West Sumatra BMT which became the object of evaluation was the health of BMT At-Taqwa Muhammadiyah West Sumatra. The data analysis technique in this study used descriptive analysis research. In this study data was collected through documentation and interview methods. The results showed that the health level of BMT At-Taqwa Muhammadiyah West Sumatra in 2014-2016 with details: (1) capital aspects in the ratio of own capital to total assets in 2014 were unhealthy criteria, 2015 to 2016 criteria were quite healthy, on the CAR ratio 2014 to 2016 with healthy criteria. (2) earning asset quality aspects on the ratio of problematic receivables and financing to 2014-2015 healthy criteria and 2016 unhealthy criteria, in the 2014-2016 earning assets elimination ratio with unhealthy criteria. (3) efficiency aspects on the ratio of operational financing to gross participation in 2014 and 2016 unhealthy criteria and in 2015 the criteria were quite healthy, in 2014-2016 fixed assets and total assets ratios the criteria were healthy, in the service efficiency ratio of 2014-2016 the criteria were not healthy. (4) the liquidity aspect in the cash ratio in 2014 and 2016 the criteria are not healthy and in 2015 the criteria were unhealthy, the ratio of funding to funds received in the year 2014-2016 was not healthy. (5) compliance with sharia principles in 2014-2016 is critically sound.